VARIASI CAIRAN PENYARI EKSTRAK DAUN PUCUK MERAH (Syzygium myrtifolium Walp.) TERHADAP BIOAKTIVITAS BAKTERI Propionibacterium acne - Imrawati, Imrawati; Kursia, Sukriani; Desiana, Desiana (JNSTA ADPERTISI JOURNAL, 2023)
Acne is a skin disease that can block the appearance of the face, neck and back of the body. Acne occurs because the liquid sebum fat is converted by the bacteria Propionibacterium acne to become denser so that it is easy to clog the skin pores. The purpose of this study was to determine the antibacterial activity of red shoots (Syzygium myrtifolium Walp.) with a variety of filter fluids against Propionibacterium acnes bacteria. The sampling technique was carried out by picking the red leaves. The results showed that the bioactivity as antibacterial of ethanol extract, ethyl acetate, and n-hexane of red shoots leaves contained tannins in the ethanol extract, flavonoids, alkaloids, tannins, saponins and steroids in the ethyl acetate extract and alkaloids, tannins, saponins and steroids in the extract. n-hexane. testing the antibacterial activity of each extract with a concentration of % obtained the great value on the n-hexane extract with an inhibitory power value of 14.5 mm with a strong category, and the results of statistical processing SPSS non-parametric method with further tests from the Kruskal Wallis Test it was found that the difference between each extract with the great value was found in the n-hexane extract, namely 14.21.